Sustainable Design Approaches of Leed-Certified Healthcare Buildings - Tavşan, Filiz; Bektaş, Umay (Journal of Interior Design and Academy, 2023)
Rapidly advancing technology and increasing consumption habits in human needs have increased production and construction. Natural resources and raw materials have been rapidly consumed and the natural environment has been destroyed. The deteriorating ecological balance has caused environmental problems. Realizing that today's humanity and future generations are under threat, the scientific world has turned to environmentalist and sustainable studies in order to prevent environmental problems. For these reasons, in this study, healthcare buildings with LEED (Leadership in Energy and Environmental Design) certificate, which is a sustainability certification system, were examined and compared under the main headings of management, energy and atmosphere, material, indoor environmental quality, water, transportation, land and ecology, innovation, pollution, waste management. As a result of the study, it was seen that LEED certified healthcare buildings prioritize materials and water and indoor quality criteria, while the use of natural resources and transportation criteria remain in the background.